CineCulture first spring film Jan. 11 inspired by Beethoven - Uribes, Tom::::::::: (2013)
Fresno State's CineCulture, in collaboration with Fresno Filmworks and the Fresno Philharmonic, will launch its spring 2013 film series with "A Late Quartet" at the Tower Theater on Friday, Jan. 11 from 5:30 to 8 p.m.